Evolving Trends in Modern History Writing: A Comprehensive Overview - Bhandari, Arjun Bahadur (HISAN: Journal of History Association of Nepal, 2023)
History is the study of human civilization across various cultures, geographical locations, and historical eras. It covers various occurrences, movements, conflicts, discoveries, and relationships that have contributed to the development of the modern world. The practice of writing history has undergone significant transformations over the years, shaped by evolving methodologies, technological advancements, and changing perspectives. Modern history writing is a dynamic field that encompasses a wide range of approaches, from traditional narrative histories to the incorporation of interdisciplinary methods. This article explores the key trends in modern history writing, highlighting the diverse methodologies employed by historians and the impact of technological innovations on the field focusing on the need for accurate documentation and transmission of history. The paper uses qualitative methods, including in-depth interviews, conversations with historians, academicians, university professors, and library research.